Current Status of Acceptance of Disability and the Correlation With the Life Quality in Parkinson's Disease in Southwest China - Liang, Yan; Chen, Dezhi; Ou, Ruwei; Zhao, Bi; Song, Wei; Yi, Xiaojiang; Yang, Rong; Chen, Xueping (Frontiers in Medicine, 2022)
Background: Acceptance of disability (AOD) is a process that a patient must undergo to cope with altered abilities, but its effect in Parkinson's disease (PD) remains unclear. The present study aimed to determine the level of AOD, examine the influence of sociodemographic variables and disease characteristics on the AOD level, and evaluate the relation between AOD level and quality of life in a cohort of PD patients in China. Methods: A total of 336 PD patients were consecutively recruited from November 2018 to October 2020. At enrollment, demographic and clinical data were obtained using a questionnaire, and the Acceptance of Disability Scale-Revised (AODS-R) scale was used to measure the AOD level. Results: The mean total score of AOD is 87.28, indicating a moderate level of disability acceptance in PD patients. Statistical analysis showed that understanding of PD, family support, and UPDRS-II or III score were major factors affecting AOD level, and patients with low AOD were more likely to have poorer quality of life. Conclusion: AOD is a serious problem in PD patients in China, especially among individuals with insufficient family support and a lack of recognition of the disease. However, patients with more severe clinical manifestations had a better disease acceptance, which significantly impacted the patients' assessment of the quality of life. Awareness of the psychological reactions and patient education should be enhanced in clinical practice. Future studies should investigate what effective psychological interventions should be implemented to improve the acceptance of disability in PD patients.